Perhubungan Terorisme dengan Kejahatan Transnasional: Crime-Terrorism oleh Kelompok Abu Sayyaf di Filipina - Maulidita, Salismi Zulfi; Novita, Fauziah; Hikmah, Indah Putri (Jurnal Sentris, 2023)
Terrorism, like other forms of criminal activities, undergoes continual adaptation in response to societal changes and the passage of time. Recent studies have begun to explore the evolving nature of criminal activities conducted by terrorist groups that concurrently function as multinational crime syndicates, often referred to as ‘crime-terrorism.’ In this particular study applied the crime-terrorism framework by Rollins and Wyler, with a specific focus on the Abu Sayyaf Group as the subject of analysis. This paper delves into the Abu Sayyaf Group's motivation for transitioning into a crime-terrorist organization and examines the tactics employed by the group in carrying out their operations. Utilizing a qualitative research methodology aligned with the principles established by John W. Creswell, this study elucidates two significant findings: (1) the Abu Sayyaf Group's motivation for engaging in organized crime is primarily driven by the need to sustain its operations and support its members' livelihoods since the external funding sources is disrupted; and (2) the tactics practiced by the Abu Sayyaf Group include bomb attacks, kidnappings, extortion, and the provision of security for illicit activities such as the cultivation and trade of illegal cannabis. Keywords: Abu Sayyaf Group; Terrorism; Transnational Crime; Crime-Terrorism